Preparation and Electrical Properties of Nanocomposite Based on Epoxy Resin and Core-Shell Polyaniline/Multi-Walled Carbon Nanotubes - Seyed Mohamad Reza Paran (Advanced Energy Conversion Materials, 2024)
Nanocomposites of epoxy resin containing various concentrations of carboxylated multiwalled carbon nanotubes (C-MWCNTs) and surface modified C-MWCNTs various concentration of both C-MWCNTs and core-shell nanoparticles were prepared. The physical, mechanical and electrical properties of prepared epoxy nanocomposites were investigated using experimental evaluations such as dynamic mechanical thermal analysis (DMTA), differential scanning calorimeter (DSC), and tensile strength measurements. The results of DSC tests revealed that the introduction of nanoparticles into the epoxy resin did not have much effect on the curing system, and by adding these nanoparticles to the epoxy resin, there is no need to change the curing system. However, the released energy during of epoxy curing show a 24% increase with the introduction of nanofiller into the epoxy matrix. The results of electrical conductivity measurements indicated a higher elastic dielectric constant for nanocomposites up to 200% incomparison with neat epoxy resin. The use of these epoxy nanocomposites in modern electrical and electro-optical industries is of great practical importance.